Challenges of the regulation of paid transportation of people through digital platforms in Costa Rica - González, Yessica Espinoza (2021)
The objective of this article is to analyze the most important aspects of digital-transportation-platforms regulation in Costa Rica, as the sector needs to balance the participation of official taxis, consumers, platforms and drivers from those platforms. This work is descriptive, and it was done under a qualitative basis. The main finding was that, even though those platforms were introduced more than 5 years ago, remaining work is left in terms of quality, pricing and labor conditions. Conciliation between key groups, an upgrade in the pricing system from official taxis and quality adjustments in the sector are part of the recommendations aiming to solve the present issues.